Pro bash programming scripting the GNU/Linux shell - Johnson, Chris; Varma, Jayant (Apress, 2015)
Pro Bash Programming teaches you how to effectively utilize the Bash shell in your programming. The Bash shell is a complete programming language, not merely a glue to combine external Linux commands. By taking full advantage of Shell internals, Shell programs can perform as snappily as utilities written in C or other compiled languages. And you will see how, without assuming Unix lore, you can write professional Bash 4.3 programs through standard programming techniques. This second edition has updated for Bash 4.3, and many scripts have been rewritten to make them more idiomatically Bash, taking better advantage of features specific to Bash. It is easy to read, understand, and will teach you how to get to grips with Bash programming without drowning you in pages and pages of syntax. Using this book you will be able to use the shell efficiently, make scripts run faster using expansion and external commands, and understand how to overcome many common mistakes that cause scripts to fail. This book is perfect for all beginning Linux and Unix system administrators who want to be in full control of their systems, and really get to grips with Bash programming.
Includes index. - Online resource; title from PDF title page (EBSCO, viewed June 24, 2015)
Keywords: Operating systems (Computers); User interfaces (Computer systems); computerwetenschappen; computer sciences; Information and Communication Technology (General); Informatie- en communicatietechnologie (algemeen); Systèmes d'exploitation (Ordinateurs); Interfaces utilisateurs (Informatique); operating systems; Software Engineering; Computer programming; software development; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference